Sources of technological knowledge and farm output: evidences from a large-scale farmers’ survey - Bibhunandini Das (Agricultural Economics Research Review, 2023)
The paper examines sources of technological knowledge and their effect on farm output in India. We find farmers accessing information on technologies from several sources involving information and communication technologies (ICT). The use of ICT however is limited to 21.8% of households and has increased over time. Further, from the econometric analysis we find that both use of ICT and non- ICTs differentiates farm output, but it is only the large farmers who realize more if they use ICTs. However, small farmers get higher return if they have access to ICT as well as non-ICT sources of information.